Contact electrodeposition of CdTe thin films - Klochko, N.P.; Volkova, N.D.; Kharchenko, M.M.; Kopach, V.R. (Functional Materials, 2009)
The effect of contact electrodeposition conditions on the impurity content in CdTe films has been studied. Stoichiometric single-phase CdTe layers of cubic modification have been obtained. The films are not texturized, and are characterized by the coherent-scattering region size of about 30 nm and the relative micro-strain values of about 5·10⁻³. Досліджено вплив контактного електроосадження на вміст домішок у плівках CdTe. Одержано стехіометричні однофазові шари CdTe кубічної модифікації . Плівки є нетекс турованими і характеризуються розміром областей когерентного розсіювання ≈ 30 нм та значенням відносних мікродеформацій ≈ 5·10⁻³. Изучено влияние условий контактного электроосаждеmrя на содержание примесей в пленках CdTe. Получены стехиометрические однофазные слои CdTe кубической модификации. Пленки не текстурированы, характеризуются размером областей когеррентного рассеяния ≈ 30 нм и значениями относительных микродеформаций ≈ 5·10⁻³.